Scutellaria Barbata inhibits epithelial-mesenchymal transformation through PI3K/AKT and MDM2 thus inhibiting the proliferation, migration and promoting apoptosis of Cervical Cancer cells - Guobing Wang; Congchao Jia; Dexin Wang; Lei Liang; Lan Li; Gang Tian; Wenqi Feng (PLoS ONE, 2025)
Background Cervical cancer is the fourth most common malignant tumor among women with high morbidity and mortality. We found the active ingredients, action targets and pathways of Scutellaria Barbata against cervical cancer cells, and verified its effects and mechanisms on the proliferation, migration and apoptosis of cervical cancer cells through cellular experiments. Materials and methods The potential effective components of Scutellaria Barbata were obtained by data mining. CCK 8 experiments were used to verify the optimal action time and concentration of the key active components, Baicalin and Wogonin on Hela cells. Transwell Experiments to verify the migration rate of Hela cells at different time points of action. Hela cell apoptosis was determined by a Tunel assay. RT-qPCR and Western Blot detection of related genes and protein expression after the effects of different concentrations of Baicalein and Wogonin on Hela cells. Results Obtained 27 core intersecting targets. Four genes associated with survival of cervical cancer patients were selected by survival by univariate analysis: EGFR, TNF-α, VEGFA and MDM2 (P<0.1). GO and KEGG pathway enrichment analysis showed the four genes played positive regulatory roles, mainly enriched in cellular extracellular zone and cytoplasm. Pathways include cancer pathways, proteoglycans and PI3K/AKT signal. CCK 8 experiments showed that the proliferation rate of Hela cells was significantly lower than that of the control group, and the optimal drug concentration was 10 mg/mL (P <0.001). The migration assay showed that the incubation of the medium with a mixture of 10 mg/mL each or 72h of 5 ml/mL each significantly inhibited the migration of Hela cells (P <0.001). Tunel results showed that single-agent Baicalein or Wogonin with 10 mg/mL had the highest rate of apoptosis on Hela cells after culturing the cells for 72 h. Baicalein or Wogonin (10 mg/mL + 10 mg/mL) had the highest apoptosis ratio in Hela cells after 72h and a higher combination ratio than in the single agent group (P <0.001). The difference between the single drug group and the corresponding low dose group was significant (P<0.001). After Hela cells were cultured for 72 h, the mRNA and protein expressions corresponding to EGFR, TNF-α, VEGFA, PI3K, AKT and MDM2 were decreased in the experimental group compared with the control group as confirmed by RT-PCR and Western blot, and the extent of the decrease was more obvious with the increase of the drug concentration, and under the condition of the same drug dosage, the effect of the Baicalein group was more pronounced than that of the Wogonin group, and the effect was more obvious in the two-drug group compared with the single-drug group (P<0.05). Conclusion After combining with EGFR, TNF-α and VEGFA, the active ingredient of Sculellaria Barbata can regulate the PI3K/AKT signaling pathway and down-regulate the expression of MDM2 gene to inhibit the epithelial-mesenchymal transition, which can inhibit cervical cancer cell proliferation, migration, and promote their apoptosis. Sculellaria Barbata is a potential therapeutic candidate for cervical cancer.